The Effect of Hedonic Shopping Motivation and Fear of Missing Out (FOMO) on Impulsive Buying Behavior: A Study of Tiktok Shop Twin Date Sales - Popy Rufaidah; Andre Bagus Pramudita (International Journal of Business Studies, 2026)
This study explores how hedonic shopping motivation and fear of missing out influence impulsive buying during the Twin Date TikTok Shop event in Indonesia. Using the adapted dimensions of hedonic shopping motivation and fear of missing out (FOMO), this study examines the behavior of TikTok Shop consumers in Indonesia upon encountering this promotional event. The primary objective is to examine and analyze consumer hedonic shopping motivation and fear of missing out and their impact on impulsive buying during the Twin Date TikTok Shop Indonesia promotion, using a set of indicators adapted from previous research. Data were collected through a survey administered to 114 TikTok Shop consumers participating in the Twin Date event. This study used Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that fear of missing out significantly influences impulsive buying, while hedonic shopping motivation influences the effect, albeit in the opposite direction. However, a limitation of this study is its focus solely on hedonic shopping motivation and fear of missing out on impulsive buying. This study ignores other potential influencing variables, such as price, product quality, and consumer preferences. Therefore, this study shows that Hedonic Shopping Motivation and FOMO contribute to Impulsive Buying during the Twin Date event on TikTok Shop in Indonesia.